The "Incongruous Stranger" as Structural Element in the Novels of Elsa Triolet - Lorene M. Birden (Studies in 20th & 21st Century Literature, 2001)
In Language in Literature, Roman Jakobson underlines the presence of a certain device, which he calls he superfluous passerby, in Russian realist literature. This element has traveled into French literature with a Russian-born expatriate novelist. Several works by Eisa Triolet present this type of character, and extend the device structurally. In this device a character can provoke a new development in plot or character relations. Such a character has no direct relationship to the characters or events portrayed. Therefore, as opposed to classic novelistic perspective, this incongruous and unknown character shifts and blurs characterial hierarchy. The superfluous passerby displaces the focus of the narrative, creating a moment of impeded perception and of diversion that makes the following event, a momentous happening in the life of the main character, foregrounded structurally in its decisiveness. This study analyses the traditional and the modernist aspects of this device, places the character within the Triolean repertoire, studies its narrative function, and defends an unjustly ignored French author. The device, which forms part of the modus operandi of Eisa Triolet, a style that her critics called réalisme fantastique, is illustrated using Zascitnyj cvet (1928), Mille regrets (1942), L'Inspecteur des ruines (1948), Luna-Park (1959), and Ecoutez-voir (1968).
Keywords: Language in Literature; Roman Jakobson; Russian realist literature; Russian Literature; Russia; French literature; Russian-born expatriate novelist; Eisa Triolet; superfluous passerby; hierarchy; character; displace; traditional; modernist; Triolean repertoire; modus operandi; réalisme fantastique; Zascitnyj cvet; Mille regrets; L' Inspecteur des ruines; Luna-Park; Ecoutez-voir